Physico-Chemical, Phytochemical and Antioxidant Evaluation of Zizyphus nummularia (Burm. F.) Stem Bark - Babita Aggarwal ,; Pankaj Sharma ,; H.S. Lamba, (Journal of Pharmacy and Nutrition Sciences, 2018)
Zizyphus nummularia (Burm. F.) (Family: Rhamnaceae) used as a folk medicine. The study was designed to lay down the various physicochemical and phytochemical standards which will be helpful to ensure the purity, safety, and efficacy of this medicinal plant. In the lime light of fewer and less potent antioxidant extracts, it is screened for antioxidant potency also. All physico-chemical properties were found within the measurable amount. Preliminary phytochemical analysis confirmed the presence of alkaloids, flavonoids, tannins and steroids. Total phenolic content and flavonoid content was found to be 10.7±0.1 and 2.57±0.1 respectively. Extract also found to posses significant antioxidant activity which can be correlated with phenolic content. IC50 of 0.042 mg/mL was found during DPPH radical scavenging activity. 2.75 mmol AA/ mg extract was found to be as total antioxidant capacity along with a concentration of 383.4 µg/ml during reducing power activity. The study would help in the authentication stem bark useful for laying down pharmacopoeial standards and help in finding improved antioxidant agents from the extract. It is found to be posse’s significant antioxidant property, possibly by adsorbing and neutralizing free radicals.